Spatial and Temporal Variations in 94-GHz Radar Backscatter From a Springtime Snowpack - William D. Harcourt; Duncan A. Robertson; David G. Macfarlane; Brice R. Rea; Mike R. James; Mark Diggins; Blair Fyffe (IEEE Journal of Selected Topics in Applied Earth Observations and Remote Sensing)
Terrestrial snow cover is a perennial feature of the mountain cryosphere and can change rapidly in response to variable weather patterns. Measuring the interaction between atmospheric conditions and a snowpack at high spatial and temporal resolution requires the use of close-range sensors. Here, we measured the variability of a spring snowpack across two corries in Scotland using ground-based 94 GHz radar in order to assess its ability to monitor snowpack changes. We deployed both the second generation All-weather Volcano Topography Imaging Sensor (AVTIS2) 94 GHz radar and a Riegl LPM-321 Terrestrial Laser Scanner in the Cairngorms National Park, Scotland, in March 2021 over 3 days. AVTIS2 is a tripod-mounted, real-aperture radar system which mechanically scans across a scene of interest to map normalized radar cross section $(σ ^{0})$ and 3-D point clouds. We measured an increase in $σ ^{0}$ of $\sim$ 10 dB over 24 h during which time the daytime (09:00–18:00) average air temperature reduced from 2.2 to 0.3 $^{° }$ C. We suggest this increase in radar backscatter was due to the transition of the snowpack from surface melting to a refrozen state. Overnight, snow drift led to the formation of windslab across the headwall of the corrie and subsequent snowpack failure, which we identified through a localized increase in $σ ^{0}$ of 10–15 dB. The high sensitivity of 94-GHz radar backscatter to changes in snow surface conditions demonstrates the capabilities of millimeter-wave radar for daily monitoring of snow cover characteristics across complex topography with a spatial resolution of approximately a few meters.